Intellectual Background of Ibn Badis and His Contribution on Societal Change in Algeria, 1913-1940 - Bensala, Youcef; Ali, Abdul Karim; Gokaru, Shuaibu Umar; Benaouali , Mohamed Cherif (Journal of Al-Tamaddun, 2024)
Abd Al-Hamid Ibn Badis was a hugely influential figure in the Islamic world. He impressed scholars both in the East and the West, with the French historian and journalist Andre Julien describing him as one of the most powerful figures of his time. The Tunisian Mufti Tahar Ibn Ashour even called him the father of Algeria’s Renaissance. In addition to exploring Ibn Badis’ impact on societal change, this study has been conducted to examine the elements of his intellectual background and how he overcame the obstacles he faced during the French colonial period. At that time, the entire country, including schools and endowments, was ruled by the French. The study highlights that Ibn Badis’ contribution to Algerian society was not only in education, but also in the economy, politics, sports, and all areas that promote human development. The study also reveals that Ibn Badis’ success in preventing the colonialists was due to his ability to exploit legal loopholes and gain support from all social classes. After they applied his educational philosophy and saw its results, people were eager to support him. France even intentionally ignored some of his works due to the possible disruption of security caused by his rising popularity. Therefore, this study recommends that Abd Al-Hamid Ibn Badis’ contribution should be implemented to add more value to human endeavours.